2005
DOI: 10.1007/b99427
|View full text |Cite
|
Sign up to set email alerts
|

Thermostat Algorithms for Molecular Dynamics Simulations

Abstract: Molecular dynamics simulations rely on integrating the classical (Newtonian) equations of motion for a molecular system and thus, sample a microcanonical (constantenergy) ensemble by default. However, for compatibility with experiment, it is often desirable to sample configurations from a canonical (constant-temperature) ensemble instead. A modification of the basic molecular dynamics scheme with the purpose of maintaining the temperature constant (on average) is called a thermostat algorithm. The present arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
337
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 472 publications
(348 citation statements)
references
References 121 publications
(237 reference statements)
3
337
0
8
Order By: Relevance
“…He established the mathematical formulation of the so called Nosé-Hoover thermostat [32][33][34][35][36][37] enabling the molecular dynamics simulation of a system to sample configurations of a canonical (constant-temperature) ensemble. It is based on the extension of the real system by an artificial dynamical time scaling variable s. This important relationship serves in the following for the establishment of the microscopic entropy of a single particle (note, that s n is the discrete analog of s).…”
Section: Scaling Of Time In Accordance To Nosémentioning
confidence: 99%
See 3 more Smart Citations
“…He established the mathematical formulation of the so called Nosé-Hoover thermostat [32][33][34][35][36][37] enabling the molecular dynamics simulation of a system to sample configurations of a canonical (constant-temperature) ensemble. It is based on the extension of the real system by an artificial dynamical time scaling variable s. This important relationship serves in the following for the establishment of the microscopic entropy of a single particle (note, that s n is the discrete analog of s).…”
Section: Scaling Of Time In Accordance To Nosémentioning
confidence: 99%
“…While this equation is in principle reversible, it is interesting to note, that it could be irreversible if the friction term is constrained to values 0. The ad hoc introduction of such a friction term is often used in classical mechanics to introduce irreversibility, stochastisity or/and to deal with the interaction of the system of interest with its surrounding as exemplified for example by the Langevin dynamics [5,37]. It is also used to describe and study the quantum mechanical decoherence phenomenon [38].…”
Section: Scaling Of Time In Accordance To Nosémentioning
confidence: 99%
See 2 more Smart Citations
“…Utilization of a single thermostat for temperature control in these solute-solvent systems leads to differences between the solvent and solute temperatures, an effect called "hot solvent -cold solute problem" [10]. This problem is normally overcome by employing one thermostat for the proteins and another for the solvent [11]. However, it has recently been [12] reported that the small differences observed between the solute and solvent temperatures upon application of a sole thermostat are due to the way the temperature is calculated and a large difference in temperature indicates a problem in the methodology.…”
Section: Introductionmentioning
confidence: 99%